2015
DOI: 10.3389/fmicb.2015.00690
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug use among individuals living with HIV in Europe: review of the prevalence, comparison with the general population and HIV guidelines recommendations

Abstract: Background: Adherence problems, interactions and higher rate of risk activities have been observed in HIV individuals using recreational drugs. Our aim was to describe recreational drug use in both HIV individuals and general population in Europe, and to assess at what extent HIV guidelines address this issue.Methods: Data on recreational drug use across Europe were obtained from the European Monitoring Centre for Drugs and Drug Addiction for the general population, and through Pubmed search. for HIV patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…This proportion is approximately twice as high as previously recorded in general samples of people living with HIV/AIDS in other North American (de Jong et al, 2005; Prentiss et al, 2004; Rosen et al, 2013) and European (Garin et al, 2015) jurisdictions, where prevalence of any cannabis more closely approximates our presently recorded median 20% prevalence of daily use. However, our estimates closely resemble those recorded in a French cohort of patients co-infected with HIV and HCV (Marcellin et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…This proportion is approximately twice as high as previously recorded in general samples of people living with HIV/AIDS in other North American (de Jong et al, 2005; Prentiss et al, 2004; Rosen et al, 2013) and European (Garin et al, 2015) jurisdictions, where prevalence of any cannabis more closely approximates our presently recorded median 20% prevalence of daily use. However, our estimates closely resemble those recorded in a French cohort of patients co-infected with HIV and HCV (Marcellin et al, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…9 Unlike the case of injecting drug users, with clear evidence of poor HIV-related outcomes and specific recommendations,10 interest in recreational drugs is recent in the HIV field. A previous, systematic review found 12 articles reporting prevalence data on recreational drug use in PLWHIV in Europe 11. Relevant use of recreational drugs was found in these studies.…”
Section: Introductionmentioning
confidence: 98%
“…Despite the potential clinical impact of recreational drug issues, guidelines on HIV antiretroviral therapy have poorly incorporated these elements 11. Guidelines tend to include general claims but usually lack specific recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data reveal higher rates of lifetime RDU relative to the general population among sexual health clinic attendees [6,11] and HIV-positive MSM attending out-patient clinics [1,3]. However, there is a distinct lack of data regarding RDU among the HIV-infected in-patient population.…”
Section: Introductionmentioning
confidence: 99%